Care Delivery Impact of the COVID-19 Pandemic on Breast Cancer Care. Issue 8 (August 2021) - Satish, Tejus; Raghunathan, Rohit; Prigoff, Jake G.; Wright, Jason D.; Hillyer, Grace A.; Trivedi, Meghna S.; Kalinsky, Kevin; Crew, Katherine D.; Hershman, Dawn L.; Accordino, Melissa K.
Abstract : PURPOSE: COVID-19 has altered healthcare delivery. Previous work has focused on patients with cancer and COVID-19, but little has been reported on healthcare system changes among patients without COVID-19. METHODS: We performed a retrospective study of patients with breast cancer (BC) in New York City between February 1, 2020, and April 30, 2020. New patients were included as were patients scheduled to receive intravenous or injectable therapy. Patients with COVID-19 were excluded. Demographic and treatment information were obtained by chart review. Delays and/or changes in systemic therapy, surgery, radiation, and radiology related to the pandemic were tracked, along with the reasons for delay and/or change. Univariate and multivariable analysis were used to identify factors associated with delay and/or change. RESULTS: We identified 350 eligible patients, of whom 149 (42.6%) experienced a delay and/or change, and practice reduction (51.0%) was the most common reason. The patients who identified as Black or African American, Asian, or Other races were more likely to experience a delay and/or change compared with White patients (Black, 44.4%; Asian, 47.1%; Other, 55.6%; White, 31.4%; P = .001). In multivariable analysis, Medicaid compared with commercial insurance (odds ratio [OR], 3.04; 95% CI, 1.32 to 7.27) was associated with increased odds of a delay and/or change, whereas stage II or III BC compared with stage I (OR, 0.38; 95% CI, 0.15 to 0.95; and OR, 0.28; 95% CI, 0.08 to 0.092, respectively) was associated with decreased odds of a delay and/or change. CONCLUSION: Almost half of the patients with BC without COVID-19 had a delay and/or change. We found racial and socioeconomic disparities in the likelihood of a delay and/or change. Further studies are needed to determine the impact these care alterations have on BC outcomes.